Microbiological quality of some commercial dairy products and cheese analogues focused on Mideast - Adam, AH; Aly Salwa, A; Saad, MF (Journal of the Hellenic Veterinary Medical Society, 2024)
Dairy products are food consumed by people of all age groups, especially children. They are highly nutritious and provide micro and macro-nutrients essential for the growth and maintenance of human health. However, they are not only nutritious for humans but also excellent growth substrates for microorganisms. Owing to insufficient animal health control, inadequate training of farmers & dairy processing workers about dairy hygiene, and weakness in the cold chain during production and storage, milk and dairy products are considered a high-risk category for potential microbial contamination. This review is considered a scarce review aimed to show the degree of microbiological quality of some varieties of dairy and non-dairy products, fermented milk, dairy cheeses, and cheese analogues, predominately in the Mideast.